Effects of Seed Rates on Seed Quality and Seed Multiplication Factor of Bread Wheat (Triticum Aestivum L.) in Early Generation Seed Classes Under Rain-Fed Conditions in Amhara Region, Ethiopia - Wasie, Tilaye Anbes; Shibie, Belayneh; Chanie, Yematew (Department of Agronomy and Horticulture, IPB University, 2025)
Seed is a vital agricultural resource for enhancing crop production and productivity. However, a variety of variables limit bread wheat seed output and quality, including an insufficient seed rate for early generation seed production. The experiment was conducted in three districts, Adet, Debre Tabor, and Enewari, over two years (2020 and 2021) under rain-fed conditions to determine the optimal seeding rate for early-generation seed classes of bread wheat. Treatments included factorial combinations of five seeding rates (50, 75, 100, 125, and 150 kg.ha-1) and two seed classes, breeder and basic seeds. A randomized complete-block design with three replications was employed. A combined study across years and locations revealed that the interaction effect of seed rate and seed class was not significant (P > 0.05) for the parameters of days to heading, days to maturity, plant height, spike length, seed yield, and seed multiplication ratio. The combined results showed that seed rate had a substantial effect on bread wheat spike length, yield, and seed multiplication ratio. Lower seed rates resulted in a higher seed multiplication ratio at all three locations. Increasing the seed rate from 50 to 150 kg.ha-1 increased seed yield from 2555.2 kg.ha-1 to 3235.2 kg.ha-1, although the difference in seed yield between 125 and 150 kg.ha-1 was statistically insignificant (p>0.05 for the combined study). Finally, seed rates as low as 125 kg ha-1 can be employed for all seed classes to boost early-generation seed output in the three locations and similar agroecologies.